Gene polymorphism in Netherton and common atopic disease. - Walley, A; Chavanas, S; Moffatt, M; Esnouf, R; Ubhi, B; Lawrence, R; Wong, K; Abecasis, G; Jones, E; Harper, J; Hovnanian, A; Cookson, W (2001)
Atopic dermatitis (AD) and asthma are characterized by IgE-mediated atopic (allergic) responses to common proteins (allergens), many of which are proteinases. Loci influencing atopy have been localized to a number of chromosomal regions, including the chromosome 5q31 cytokine cluster. Netherton disease is a rare recessive skin disorder in which atopy is a universal accompaniment. The gene underlying Netherton disease (SPINK5) encodes a 15-domain serine proteinase inhibitor (LEKTI) which is expressed in epithelial and mucosal surfaces and in the thymus. We have identified six coding polymorphisms in SPINK5 (Table 1) and found that a Glu420-->Lys variant shows significant association with atopy and AD in two independent panels of families. Our results implicate a previously unrecognized pathway for the development of common allergic illnesses.